TRANSFORMATIONAL LEADERSHIP, PERCEIVED ORGANIZATIONAL SUPPORT, JOB SATISFACTION TOWARDS ORGANIZATIONAL COMMITMENT - Sylviani, Sany (JURNAL ILMU MANAJEMEN, 2023)
Organizational commitment is an important factor for an organization's success in achieving its goals. Therefore, having highly committed employees is the expectation of every organization. Understanding the aspects to increase employees' commitment especially from Gen Z, will help management in policies and decisions making to improve its performance. The purpose of this study is to analyze the influence of transformational leadership, perceived organizational support, and job satisfaction towards employees' organizational commitment in a growth and developmental clinic. Quantitative method was used in this study with an online questionnaire as the research instrument. The subjects of this study are 32 clinic employees from 3 branches. PLS-SEM with Smart PLS 4.8.5 program was used for data processing. The results of this study show that transformational leadership has a positive effect on job satisfaction, transformational leadership has a positive effect on organizational commitment, perceived organizational support has a positive effect on job satisfaction, perceived organizational support has a positive effect on organizational commitment, and job satisfaction has a positive effect on organizational commitment.